การวิเคราะห์ค่าโดยสารของรถโดยสารประจำทางเส้นทางตาก - แม่สอด - รัตนพงษ์ ชังชั่ว (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Highway No. 12 (Tak–Mae Sot) is the main route traveling between Muang Tak District and Mae Sot District in Northern region of Thailand. This road is very unique because it is a winding and steep road. This unique characteristics cause the bus operators travelling on this route encounters higher operating costs than those on other routes. This research investigated how much the vehicle operating costs are and analyzed how much the fares should be for the fixed-route bus services along this route. This research consists of three tasks. First, the survey was conducted to acquire information of the cost components of bus operators on Tak–Mae Sot route. The results revealed that the costs of the bus operators on Tak–Mae Sot route were primarily the variable costs, which accounts for 67.3% of the total costs; followed by the semi-variable/semi-fixed cost (24.3%) and the fixed cost (8.4%). Second, the bus fares were analyzed according to the price structure proposed by the Department of Land Transport. The estimated fares derived from the Department of Land Transport structure were two types. One is the nationwide fare and the other is the regional fare. The study estimated the nationwide fare as 78 and 81 baht. The former represents the fare of the fixed-route van service from 2008 onward; and the latter represents the fare estimated with respect to the actual oil price in the current year (Year 2014). The study also estimated the regional fare as 96 baht, which is the fare derived from the cost data from the enterprises in the study area. Finally, the bus fares were investigated from passengers and the public viewpoints by using the willingness-to-pay analysis. The research conducted the questionnaire surveys to determine the affordable bus fares. The results showed that the fares are within the range of 78-113 baht. Based on the Kishi’s Logit Price Sensitivity Measurement, the lowest affordable fare was 78 baht; the suitable (reasonable) fare was 88 baht; the expensive (affordable) fare was 94 baht; and the most expensive (unaffordable) fare was 113 baht. The fare of fixed-route bus services for Tak–Mae Sot route should be within the range of 89 to 113 baht. If the minimum value is the breakeven point of the operators and the maximum value is the breakeven point of passengers and the public. The fare recommended by the fare structure of the Department of Land Transport is affordable for passengers and acceptable for bus operators.